Phase II study of imatinib‐based chemotherapy for newly diagnosed BCR‐ABL‐positive acute lymphoblastic leukemia. Issue 4 (21st February 2017) - Fujisawa, Shin; Mizuta, Shuichi; Akiyama, Hideki; Ueda, Yasunori; Aoyama, Yasutaka; Hatta, Yoshihiro; Kakihana, Kazuhiko; Dobashi, Nobuaki; Sugiura, Isamu; Onishi, Yasushi; Maeda, Tomoya; Imai, Kiyotoshi; et al.
Abstract: This study investigated the efficacy of imatinib based therapy with intensified consolidation therapy in patients with Philadelphia chromosome (Ph)‐positive acute lymphoblastic leukemia (ALL) to prevent early relapse. We conducted a phase II trial of imatinib‐combined chemotherapy for newly diagnosed BCR‐ABL‐positive ALL in adults. Sixty‐eight patients were included in the trial between October 2008 and December 2010. The median age was 49 years, with 28 patients >55 years of age. Sixty‐five patients achieved CR (95.6%). The estimated 2‐year event‐free survival (EFS) and overall survival (OS) were 62.3% and 67.4%, respectively. Allogeneic stem cell transplantation (allo‐SCT) at initial CR was performed in 43 patients. Thirty‐five of 39 patients <55 years and 8 of 26 patients >55 years underwent allo‐SCT at first CR. The 3‐year OS in patients <55 years receiving allo‐SCT at first CR, patients >55 years receiving allo‐SCT at first CR, patients <55 years not receiving allo‐SCT at first CR, and patients >55 years not receiving allo‐SCT at first CR were 80.4%, 41.1%, 32.5%, and 52.0%, respectively ( P = 0.058). The three‐year EFS in each group was 76.7%, 53.6%, not reached, and 26.4%, respectively ( P = 0.150). A high CR rate was observed with imatinib‐based chemotherapy allowing allo‐SCT in a high proportion of patients, particularly those <55 years. Moreover, intensified consolidation therapy reduced early relapse rates following induction therapy and resulted in improved OS and EFS rates following allo‐SCT. This trial was registered with the UMIN (000001226).